Effect of roof modifications on micro-climate in loose housing system of lactating Murrah buffaloes - Pulkit Chugh, Sandeep Dhillod, Rakesh Nehra, Narender Singh, Man Singh, Devender Singh Bidhan, Vishal Sharma, Dipin Chander Yadav; Anil Kumar (Indian Journal of Dairy Science, 2026)
The purpose of this study was to assess how well roof modifications—more especially, false ceilings composed of glass wool and expanded polyethylene (EPE) sheets painted with reflective white paint—could reduce heat stress and enhance the microclimate in the loose housing system of lactating Murrah buffaloes in subtropical climates. The experiment was conducted at the Buffalo Farm, LUVAS, Hisar, India, for ninety days. An asbestos roof without any modifications (T1, control), an asbestos roof with a glass wool false ceiling and white paint (T2), and an asbestos roof with an EPE sheet false ceiling and white paint (T3) were the three treatments that were compared. The temperature of the internal shed, relative humidity (RH), upper roof temperature (URT), false ceiling temperature (FCT), and floor temperature (FT) were recorded on a fortnightly basis for 3 consecutive days, along with macroclimatic parameters. The findings indicated that T2 had the best thermal insulation and heat reflectance, maintaining significantly (P<0.05) the lowest interior, upper roof, false ceiling, and floor temperatures with the most stable relative humidity. T1 displayed the highest temperatures and the most heat stress, whereas T3 performed in the middle. T2 considerably moderated thermal load by achieving a temperature reduction of 4–7°C in comparison to the macroclimate. According to the research, dairy buffaloes’ thermal comfort is significantly increased by integrated roof insulation and reflective surfaces, which improves their welfare and productivity in hot climates.